Antibiotic susceptibility among under-fives with severe pneumonia: a prospective study - Palanivel, Loganathan; Sivaprakasam, Chidambaranathan; Palanisamy, Logesvar (International Journal of Contemporary Pediatrics, 2018)
Background: In underdeveloped countries, lower respiratory tract infection (LRTI) remains the leading cause of under-five mortality. Judicious use of antibiotics prevents the emergence of multidrug resistant organisms, but appropriate selection is vital in the child requiring intensive care. Methods: The study in conducted prospectively in the paediatric wards and intensive care unit, Rajah Muthiah Medical College and Hospital, Chidambaram. Fifty children were enrolled in the study using simple random sampling. Data regarding the demographic details, mean duration of stay, antibiotics given, immunisation status, intensive care unit admission and complications were collected. Statistical analysis is done using the Microsoft excel 2010. Results: The complications (n=3) is more among the female children (n=2) belonging to the age group one to two years (n=2) with mean duration of stay of more than seven days (n=2) and non-immunized for age children (n=3). Conclusions: The gram positive and atypical pneumonia in Chidambaram is found to be sensitive to aminopenicillin with penicillinase resistant penicillin and macrolide respectively.